2017
DOI: 10.29359/bjhpa.09.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Application of the EEG Biofeedback method in attention deficits therapy in young sportspeople - A pilot study

Abstract: BackgroundWhile working with contestants, sports psychology has been successfully applying the biofeedback (neurofeedback) method since 1970s, noticing its potential in the field of attention concentration, decrease in destructive tension hindering achievement of the expected results in various sports disciplines. The researchers aimed at demonstrating to what extent the EEG Biofeedback method may prove useful in correcting attention concentration deficits in young sportspeople). The presented research project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Research has largely demonstrated that focusing outside the body and on the intended outcome of the movement (i.e., external focus) yields better results in learning and movement performance than focusing on body parts, specific movements, or mechanics (i.e., internal focus) ( Neumann, 2019 ). External attentional focus has been shown to result in increased movement efficiency (e.g., reduced muscle activity, higher peak force), movement performance (e.g., better balance, greater accuracy, greater speed, better endurance), a better movement form, as well as more automatic and fluent movements ( Artymiak et al, 2017 ; Razaghi et al, 2020 ; Wulf and Lewthwaite, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has largely demonstrated that focusing outside the body and on the intended outcome of the movement (i.e., external focus) yields better results in learning and movement performance than focusing on body parts, specific movements, or mechanics (i.e., internal focus) ( Neumann, 2019 ). External attentional focus has been shown to result in increased movement efficiency (e.g., reduced muscle activity, higher peak force), movement performance (e.g., better balance, greater accuracy, greater speed, better endurance), a better movement form, as well as more automatic and fluent movements ( Artymiak et al, 2017 ; Razaghi et al, 2020 ; Wulf and Lewthwaite, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of EEG signals, captured using electrodes placed on the subject's scalp, is graphically presented and displayed on a monitor screen, providing feedback on the current changes occurring in their brain. The core principle of EEG biofeedback lies in the assumption that the brain's bioelectrical activity reflects the subject's emotional states and can be controlled and modified through training ( Artymiak et al, 2017 ; Salimnejad et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%